Study of Antidepressant-Like Effects of Albiflorin and Paeoniflorin Through Metabolomics From the Perspective of Cancer-Related Depression - Zhao, Danping; Zhang, Jianjun; Zhu, Yingli; He, Cheng; Fei, Wenting; Yue, Na; Wang, Chenglong; Wang, Linyuan (Frontiers in Neurology, 2022)
Mental health has become a new challenge in cancer treatment, with a high prevalence of depression in patients with cancer. Albiflorin(AF) and paeoniflorinn(PF) are isomers extracted from the root of Paeoniae Radix Alba(Baishao in Chinese), belonging to the monoterpene glycosides, and multiple studies have been conducted on their anti-depression and anti-cancer effects. However, the effects of AF and PF on cancer-related depression are unclear. Therefore, the current study aims to investigate whether the two isomers are able to exert antidepressant-like effects and understand the underlying mechanisms in a rat model, established by combining irradiation with chronic restraint stress and solitary confinement. Our results demonstrate a significant regulation of AF and PF in the pharmacodynamic index, including the peripheral blood, organ index, behavioral traits, and HPA axis, relative to control rats. In serum and cerebral cortex metabonomics analysis, AF and PF showed a significantly restorative trend in abnormal biomarkers and regulating ether lipid metabolism, alanine, aspartate, glutamate metabolism, tryptophan metabolism, carnitine metabolism, arachidonic acid metabolism, arginine and proline metabolism pathway. Eight potential biomarkers were further screened by means of receiver operating characteristic (ROC) analysis. The data indicate that AF and PF could effectively ameliorate a depression-like state in the model rats, and the mechanism may be associated with the regulation of the neuroendocrine immune system and disrupted metabolic pathways. Further experiments are warranted to comprehensively evaluate the antidepressant effects of AF and PF in cancer-related depression. This study provides a better insight into the action mechanisms of anti-depression of TCM, and provides a new perspective for the therapy of cancer-related depression.